PARADOKS PEMAKZULAN PRESIDEN/WAKIL PRESIDEN DALAM PRINSIP NEGARA HUKUM - M. Saoki Oktava; Riska Ari Amalia (Universitas Muhammadiyah Mataram, 2019)
The promulgation of the implementation of the Constitutional Court's decision is in the spotlight of other State Institutions that have repealed articles that have been canceled by the Constitutional Court in the new Law. Likewise with the authority of the Constitutional Court. In the process of presidential impeachment by the MPR there are indications that the Constitutional Court's Decision stating that the president and / or vice-president were proven guilty by the Constitutional Court can also be set aside, given the political process in the MPR which refers to the minimum decision-making conditions. The president is attended by at least ¾ of the total number of MPR members and is approved by at least 2/3 of the total members present. The research method used is a normative research method with the statue approach approach. Sources and Types of Legal Materials namely primary legal materials, secondary legal materials and tertiary legal materials related to this study. From the results of the study, the paradox of the presidential impeachment in the principle of the rule of law, the process of presidential impeachment according to the 1945 Constitution of the Republic of Indonesia NRI is carried out by political and legal mechanisms. The Basic Strength of the Constitutional Court Decision in the Context of Presidential Decree In State Principles is Article 1 paragraph 3 of the 1945 Constitution of the Republic of Indonesia NRI